Awareness and practices of Universiti Teknologi MARA (UiTM) students towards Internet security / Azmirul Firdaus Azman - Azman, Azmirul Firdaus (Universiti Teknologi MARA Sarawak,Kampus Samarahan, 2015)
The growth of the internet over the past decade has been one of mankind's greatest achievements. The rapid growth of the internet has made people become more dependent on it. It is vital for users to fully understand the threat that they face while surfing the internet. This understanding and the knowledge of the threat can help users to protect not only their computer and other digital medium but also their personal information stored and available on the internet. People not only use the internet to communicate but also they use it for information searching, social media surfing, entertainment, internet transaction, e-commerce, digital marketing and online education (Sandesh, 2012). All of this activities done using internet will expose users directly towards the threat of hackers or viruses. Internet security will act like an umbrella that will cover your computer from all the threats. Various anti-viruses application can be used to protect the user's computer and other digital medium as well as their personal information (Karishma Sundaram, 2010). Forthis research, all respondents are students chosen from UiTM Samarahan. Research is done to investigate student's awareness and practices towards internet security.